MANAJEMEN REDAKSIONAL DAN EKSISTENSI SURAT KABAR LOKAL [Studi Kasus tentang Manajemen Keredaksian Harian Umum Flores Pos Tahun 2013] - , MAYELUS DORI BASTIAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Essence of Flores Pos as a local daily newpapers today to be main source information in fact of exist in lack of community and more competitive of local daily newspaper in NTT. This reality support working of editorial management by Flores Pos professionally in surviving of existence to the future. Flores Pos owned special characteristics from media ownership are managed by Catholic Church vis a vis SVD or form media content vis a vis renewed new inovation in editorial policy since September 2006. This research use case study analysis method in qualitative and quantitative data of descriptive in written or oral from teamwork dan their behaviour can be observed and need informan to explore data and facts of the phenomenon. This object is Flores Pos Daily Newspaper. This subject is editorial team. Technique of data collecting done through observation, interview dan library study. Technique of data analysis through steps of data collecting, reducing data, data persentation and make conclusion. This results shows that first, editorial policy of Flores Pos have designed concept and making editorial strategy to long term. Second, in news reporting Flores Pos choose to accomodate public interest. Third, to co-existence it, Flores Pos editorial always priority actuality, proximity and objective on every reportage. Fourth, Flores Pos claim that idealism and vision - mission as same as with SVD to be main standar to process of its management journalism products.